Quantum Modeling of Complex Molecular Systems - Rivail, Jean-Louis; Ruiz-Lopez, Manuel; Assfeld, Xavier (Challenges and Advances in Computational Chemistry and Physics, 2015)
This multi-author contributed volume includes methodological advances and original applications to actual chemical or biochemical phenomena which were not possible before the increased sophistication of modern computers. The chapters contain detailed reviews of the developments of various computational techniques, used to study complex molecular systems such as molecular liquids and solutions (particularly aqueous solutions), liquid-gas, solid-gas interphase and biomacromolecular systems. Quantum modeling of complex molecular systems is a useful resource for graduate students and fledgling researchers and is also an excellent companion for research professionals engaged in computational chemistry, material science, nanotechnology, physics, drug design, and molecular biochemistry.